Titik Singgung Hukum Islam dengan Hukum Adat pada Naskah Perundang-Undangan Kerajaan Islam di Nusantara - Masykhur, Anis (Al-Manahij: Jurnal Kajian Hukum Islam, 2020)
The study of the intersection of Islamic law with customary law in the legislation texts of the Islamic kingdoms in the Indonesian Archipelago is intended to describe the flexibility of Islamic law when it meets customary law, and vice versa. This research is a comparative study between the laws that were made into the sultanate law in the archipelago in the 16-18 century AD. The nature of Islamic law is believed to have the ability to adapt (legal adaptability) with other laws. One theory that can strengthen this statement is the existence of one of the five major principles in the science of Usul al-Fiqh, namely "al-Ê»adÄh al-muhakamah" which means that customs can be used as a legal basis. Ibn al-Qayyim also introduced the rule of "taghayyur al-fatwÄ bi taghayyur al-azminah", meaning changes in fatwas due to changes in time. These principles reinforce the flexibility of Islamic law. By taking some examples from articles from the Malacca law, the Simbur Tjahaya Act of the Palembang Sultanate, the Jambi Customary Law, the Sultan Adam Law on the Banjar Sultanate, the Martabat Tujuh Law for the Buton Sultanate and the Baraja Niti Kutai Law Kartanegara, it was found that the intersection between Islamic law and customary law was seen in these laws, which were complementary, and there was no tension.